2020
DOI: 10.1055/s-0040-1713625
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study on Aeroallergen Sensitivity Pattern in Children with Bronchial Asthma and/or Allergic Rhinitis

Abstract: Background The growing prevalence of allergy and asthma in India has become a major health concern, with symptoms ranging from mild rhinitis to severe asthma, and aeroallergens play a major role in the pathogenesis of reactive airway diseases. The distribution of aeroallergen and the knowledge of allergen sensitivity pattern in northern India (Rajasthan) are limited. The aim of our study was to determine the prevalence of various aeroallergens in children with bronchial asthma and/or allergic rhinitis by skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In a study conducted in a tertiary care centre in Rajasthan including 60 children with respiratory allergic diseases between 5 and 15 years, overall highest percentage of SPT positivity was found among HDM (66.6%), storage mite (41.6%), wheat (33.3%), animal dander (30%), and Kentucky bluegrass (26.6%). 722 Another study performed amongst 180 children (5-18 years) in a tertiary care centre in North India demonstrated that 100 children (55.6%) were sensitized to at least one aeroallergen, suggesting atopy. 381 A crosssectional, observational study was conducted to study the type of allergic sensitivity in a pediatric population in Hyderabad and 67% of patients were found to be sensitive to aeroallergen but 33% had a negative SPT.…”
Section: Raj Kumar Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in a tertiary care centre in Rajasthan including 60 children with respiratory allergic diseases between 5 and 15 years, overall highest percentage of SPT positivity was found among HDM (66.6%), storage mite (41.6%), wheat (33.3%), animal dander (30%), and Kentucky bluegrass (26.6%). 722 Another study performed amongst 180 children (5-18 years) in a tertiary care centre in North India demonstrated that 100 children (55.6%) were sensitized to at least one aeroallergen, suggesting atopy. 381 A crosssectional, observational study was conducted to study the type of allergic sensitivity in a pediatric population in Hyderabad and 67% of patients were found to be sensitive to aeroallergen but 33% had a negative SPT.…”
Section: Raj Kumar Et Almentioning
confidence: 99%
“…744,777 The literature reveals that the maximum number of allergens tested in children below 5 years of age were 5-15 (Table 16). 359,722 Some guidelines recommend the maximum number of skin tests which can be done at a time as 70 prick/puncture and 40 intra-cutaneous tests for inhalant allergens and ≤30 for patients who have a history of anaphylaxis during the The Indian Journal of Chest Diseases & Allied Sciences testing. 777 While others state that relatively small allergen panels (e.g., 8-12 inhalant allergens) would usually be considered adequate for the testing by general practitioners or in the respiratory laboratories.…”
Section: How To Choose Antigens?mentioning
confidence: 99%
See 1 more Smart Citation